Calcination of Various Eggshell Wastes into CaO Heterogeneous Catalysts - Dona Kurniawati Dewi; Vira Mawardha Putri; Vita Febriyanti; Cornelius Satria Yudha (Equilibrium Journal of Chemical Engineering, 2023)
Abstract. The high food industry waste can cause pollution including a pungent odor and the emergence of bacteria that cause disease. Egg shells are confectionery waste that is commonly found in household waste and the food industry. The accumulation of eggshell waste can cause various diseases such as abdominal pain, diarrhea, fever, and cramps in the stomach caused by Salmonella bacteria. Thus, further processing of egg shells is required. In this study, eggshell waste was processed into heterogeneous catalysts of CaO. This heterogeneous CaO catalyst has the potential to be used as a catalyst in the manufacture of biodiesel. In this process, egg shells are processed by the calcination method. The variables used are shell type and calcination temperature. The shell variables used were chicken egg shells, duck egg shells, and quail egg shells. While the temperature variables used are at temperatures of 600 ºC and 800 ºC. To determine the quality of heterogeneous CaO catalyst, characteristic tests were varied out in the form of SEM-EDX and FTIR. From the analysis, the most effective results were in the form of chicken eggshell variables at a calcination temperature of 800 ºC.Keywords:Calcination, CaO, Catalyst, Shell, Waste